2022
DOI: 10.1126/science.adc9831
|View full text |Cite
|
Sign up to set email alerts
|

Soybean photosynthesis and crop yield are improved by accelerating recovery from photoprotection

Abstract: Crop leaves in full sunlight dissipate damaging excess absorbed light energy as heat. This protective dissipation continues after the leaf transitions to shade, reducing crop photosynthesis. A bioengineered acceleration of this adjustment increased photosynthetic efficiency and biomass in tobacco in the field. But could that also translate to increased yield in a food crop? Here we bioengineered the same change into soybean. In replicated field trials, photosynthetic efficiency in fluctuating light was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 45 publications
4
149
0
1
Order By: Relevance
“…Therefore, the finding of faster recovery of ΦPSII conveyed by the Bur-0 plasmotype to be associated with faster relaxation of ΦNPQ implies there is not merely a difference in activation of NPQ but also in actual dissipation. Hence the variation causal to the faster recovery of ΦPSII is promising for potential photosynthetic improvements, as has been experimentally shown (Kromdijk et al, 2016;De Souza et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the finding of faster recovery of ΦPSII conveyed by the Bur-0 plasmotype to be associated with faster relaxation of ΦNPQ implies there is not merely a difference in activation of NPQ but also in actual dissipation. Hence the variation causal to the faster recovery of ΦPSII is promising for potential photosynthetic improvements, as has been experimentally shown (Kromdijk et al, 2016;De Souza et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Chen et al (2019) introduced exogenous glycolate catabolic pathway into cucumber and obtained transgenic plants that can exhibit high photosynthetic efficiency under low-CO 2 environment. De Souza et al (2022) overexpressed VPZ gene in soybean, which effectively improved the efficiency of photosynthesis. Specifically, it resulted in a 33% increase in soybean yield (De Souza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…De Souza et al (2022) overexpressed VPZ gene in soybean, which effectively improved the efficiency of photosynthesis. Specifically, it resulted in a 33% increase in soybean yield (De Souza et al, 2022). However, with overexpression of SBP or FBA in plants, the improvements in photosynthesis and biomass yield occurred only under elevated CO 2 conditions (Rosenthal et al, 2011;Uematsu et al, 2012), such improvements are significant in greenhouse environments in winter (Rosenthal et al, 2011), the authors of these studies attribute the results to the shorter day length and the lower light level.…”
Section: Discussionmentioning
confidence: 99%
“…The energy losses due to photosynthesis regulatory mechanisms can be particularly impactful in the case of light fluctuations, when NPQ and the xanthophyll cycle are activated during light peaks and remain active when the illumination decreases. In plants it has been shown that accelerating the kinetics of the xanthophyll cycle can lead to a remarkable increase in photosynthetic productivity in the field (14,15). Unicellular algae, like all other photosynthetic organisms, are exposed to light fluctuations in nature and have multiple mechanisms to modulate their photosynthetic efficiency, including NPQ and the xanthophyll cycle (16,17).…”
Section: Introductionmentioning
confidence: 99%